Виконання рекрутської повинності міським населенням Волинської губернії (кінець XVIII – 1860-ті роки ХІХ ст.). - Карліна, Оксана Миколаївна; Karlina, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проаналізовано виконання рекрутської повинності міщанами-християнами Волинської губернії на підставі законодавчих актів та діловодної документації місцевих органів влади. Показано, яке місце в організації наборів рекрутів займала міщанська громада. З’ясовано причини поширення та особливості проведення рекрутських наборів серед громадян й однодворців, які мешкали в містах і містечках.Based on the analysis of legislative acts and record keeping documentation of the local authorities the process of the execution of the recruiting duty by Christian population of the cities and towns of the Volyn province before its replacement by common military duty is traced. The author shows the place occupied by a philistine community in the organization of the recruit sets and the principles it was guided sending one or the other of its members to a long-term military service. The reasons for the distribution and the specifics of the conducted recruit sets among two other tax-paying states (citizens and smallholders) lived in cities and towns were clarified.
The Execution of the Recruiting Duty by the Urban Population of the Volyn Province (the End of the XVIII - the 1860s of the XIX Century)
Keywords: Російська імперія; Волинська губернія; рекрутська повинність; рекрутський набір; міщани- християни; Russian Empire; Volyn province; recruiting duty; recruit set; Christian philistines